Volatilidade, alavancagem e regionalidade: uma análise das empresas da América Latina - Rosa, Arthur Antonio Silva (2020)
The volatility of the stock returns consists of a measure that reflects the risk of the assets in such a way that their understanding allows a greater adequacy of the investor profiles in relation to the risk-return. On the other hand, in companies' leverage decisions, managers must consider, for example, tax benefits, but in a way that does not affect the company's ability to meet its obligations. In this sense, the literature indicates that leverage decisions affect the volatility of the company's assets. Therefore, this dissertation aims to analyze the relationship between volatility and the level of leverage of companies in Brazil and Latin America, from January 2, 2005 to June 30, 2020. The study also analyzed the volatility of Latin American and Brazilian actions and the possible influences of regionality aspects on the volatility and leverage decisions of companies. For this, the methodology used was the GMM with the data displayed in a panel, having been the volatility estimated by the EGARCH model, in addition to the use of six leverage measures. The results show that companies that increase leverage tend to increase volatility if their assets are due to the company's increased market risk. Furthermore, the 2020 pandemic presented itself as the most volatile period for Latin American actions. In relation to regionality, companies located in the Triângulo Mineiro region tend to show greater volatility due to the difficulty of monitoring these companies. In this study, it was also found that economic policy uncertainty has a positive relationship with leverage and a negative relationship with the volatility of Brazilian companies. The study contributes to the advancement of the literature by analyzing the relationship between volatility and leverage in the context of Latin American and Brazilian companies. In addition, this research differs from the others in the way of estimating volatility, as well as in the use of six leverage measures, also considering the influences of macroeconomic variables. For future studies, it is suggested to compare the results between emerging and developed countries. It is also suggested to use other metrics to estimate volatility, such as the DCC-GARCH and PARCH.